Augmenting productivity and profitability through Sesame–Legume intercropping - Fiseha Baraki; Zenawi Gebregergis; Goitom Teame; Yirga Belay (Heliyon, 2023)
Introduction: Intercropping contributes a significant role in sustainable agricultural system as it improves soil conservation, productivity and stability of yield and makes better use of production elements. However, the economic advantages and dis advantages of sesame and legume intercropping is not quantified. Methods: Field experiment, consisted of seven treatments, conducted in 2016 and 2017 cropping seasons using randomized complete block design with three replications. Land equivalent ratio, Competitive Ratio (CR), Relative crowding coefficient (K), Aggressivity (A), Sesame equivalent yield, Legume equivalent yield (LEY), Monetary Advantage Index, Area Time Equivalent Ratio (ATER), Land Saved and correlation of the indexes were competed. Results: The highest total LER (0.63) recorded from sesame intercropped with half as well as full seed rate of mungbean. Sesame intercropped with half seed rate of mungbean showed lower CR (1.57) and the total K of the system was greater than a unity in three of the treatments except in sesame + half seed rate of soybean with total K of 0.81. Sesame intercropped with half seed rate of soybean was dominant with aggressivity (0.13) while it was dominated in both of the other treatments with negative aggressivity. The highest MAI (1181.15 and 1239.1) was gained from sesame intercropped with mungbean at full and half seed rates respectively and the ATER value of sesame + half seed rate of soybean was greater than a unity while sesame + half seed rate of soybean scored lower than unity (0.94). Grain yield showed a positively strong correlation with LEY, SEY, and Ktot while it showed a negative correlation with CRs and As. Based on the PCA biplot the intercropping indexes grouped in to three clusters (I-III): cluster I, II and III consisted of 3, 1 and 9 intercropping indexes respectively. Conclusion: LS, LER and MAI are the best indexes to compute the economic profitability of a mixed cropping. Generally, based on the LS, LER and MAI sesame-legume intercropping practice is economically profitable.